1994
DOI: 10.1046/j.1471-4159.1994.62062246.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies with Substance P Analogues: Effects of N‐Terminal, C‐Terminal, and C‐Terminus‐Extended Analogues of Substance P on Nicotine‐Induced Secretion and Desensitization in Cultured Bovine Adrenal Chromaffin Cells

Abstract: Substance P (SP) and SP analogues, including C-terminal, N-terminal, and C-terminus-extended analogues, have been investigated for their ability to modulate nicotine-induced secretion from bovine adrenal chromaffin cells in culture. Secretion was monitored by measuring the release of endogenous catecholamines by electrochemical detection following separation on HPLC and the release of endogenous ATP with an on-line luciferin-luciferase bioluminescence technique. SP is known to have the following two effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition to CAT, substance P is another neuro-immunomodulator that may inhibit nicotinic cholinergic-stimulated catecholamine release, but displays a lower potency [70]. PACAP displays numerous functions in cells of neuronal and non neuronal origin and functional VIP/PACAP receptors have been demonstrated on PMNs, mediating Ca 2+ - dependent pro-inflammatory activities through the activation of multiple regulatory pathways [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CAT, substance P is another neuro-immunomodulator that may inhibit nicotinic cholinergic-stimulated catecholamine release, but displays a lower potency [70]. PACAP displays numerous functions in cells of neuronal and non neuronal origin and functional VIP/PACAP receptors have been demonstrated on PMNs, mediating Ca 2+ - dependent pro-inflammatory activities through the activation of multiple regulatory pathways [71].…”
Section: Discussionmentioning
confidence: 99%
“…For a more in-depth investigation of postsynaptic attack, studies were performed on isolated chromaffin cells with Bruce Livett (Melbourne) ( 14 ) to understand the modulation of synaptic transmission in these cells. This showed that SP has two effects.…”
Section: Pharmacological Actions Of Substance Pmentioning
confidence: 99%